THE EFFECT OF ENERGY LEVEL OF FEEDING ON DAILY GAIN, BLOOD GLUCOSE AND UREA ON MADURA CATTLE - Umar, M.; Kurnadi, B.; Rianto, E.; Pangestu, E.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
This study was aimed to evaluate the effect of dietary energy level on daily gain of Madura cattle and their blood metabolites (glucose and blood urea). Twelve (12) male Madura cattle aged at 2 years old, 156.27+6.92 kg (CV 4.43%) of body weight were used in this study which was assigned to completely randomized design for three feeding treatments (low, middle and high energy contents) and four replications. The daily gain was measured for 90 days, while the blood metabolites were measured at the middle of experiment. Results showed that dietary energy levels did not affect (P>0.05) average daily gain, dry matter intake, dry matter digestibility, energy intake and feed conversion ratio. Blood glucose and blood urea concentration were ranged at 67-75 and 35-50 mg/dL, respectively, while feed energy efficiency reached 0.145 MJ/g ADG. In conclusion, high-level energy could not provide better performance in Madura cattle because of a limitation factor on the DMI.